The frequency and outcome of lupus nephritis: results from an international inception cohort study - Hanly, John G.; O’Keeffe, Aidan G.; Su, Li; Urowitz, Murray B.; Romero-Diaz, Juanita; Gordon, Caroline; Bae, Sang-Cheol; Bernatsky, Sasha; Clarke, Ann E.; Wallace, Daniel J.; Merrill, Joan T.; Isenberg, David A.; et al. (Rheumatology (Oxford, England), 2016)
To determine nephritis outcomes in a prospective multi-ethnic/racial SLE inception cohort. Patients in the Systemic Lupus International Collaborating Clinics inception cohort (≤15 months of SLE diagnosis) were assessed annually for estimated glomerular filtration rate (eGFR), proteinuria and end-stage renal disease (ESRD). Health-related quality of life was measured by the Short Form (36 questions) health survey questionnaire (SF-36) subscales, mental and physical component summary scores. There were 1827 patients, 89% females, mean (s.d.) age 35.1 (13.3) years. The mean (s.d.) SLE duration at enrolment was 0.5 (0.3) years and follow-up 4.6 (3.4) years. LN occurred in 700 (38.3%) patients: 566/700 (80.9%) at enrolment and 134/700 (19.1%) during follow-up. Patients with nephritis were younger, more frequently men and of African, Asian and Hispanic race/ethnicity. The estimated overall 10-year incidence of ESRD was 4.3% (95% CI: 2.8%, 5.8%), and with nephritis was 10.1% (95% CI: 6.6%, 13.6%). Patients with nephritis had a higher risk of death (HR = 2.98, 95% CI: 1.48, 5.99; P = 0.002) and those with eGFR <30 ml/min at diagnosis had lower SF-36 physical component summary scores (P < 0.01) and lower Physical function, Physical role and Bodily pain scores. Over time, patients with abnormal eGFR and proteinuria had lower SF-36 mental component summary (P ≤ 0.02) scores compared to patients with normal values. LN occurred in 38.3% of SLE patients, frequently as the initial presentation, in a large multi-ethnic inception cohort. Despite current standard of care, nephritis was associated with ESRD and death, and renal insufficiency was linked to lower health-related quality of life. Further advances are required for the optimal treatment of LN.